The impact of macrophage infiltration on [18F]FDG PET accuracy in identifying mediastinal and abdominal lymph node metastases: A retrospective cohort study - Jing Wei; Weijing Tao; Tianshuo Yang; Jie Dong (PLoS ONE, 2026)
This study aimed to comprehensively analyze the complex interaction between the presence of macrophages and [ 18 F]FDG PET findings. This retrospective study enrolled 240 patients with histologically confirmed malignancies. Patients underwent histopathological examinations of excised lymph nodes, with CD163 staining to quantify M2 macrophage infiltration, which was used to stratify patients into high and low infiltration groups. Data collection encompassed demographic, clinical, imaging, and histological data. High infiltration group had a longer disease duration compared to the low infiltration group (p < 0.001). [ 18 F]FDG PET imaging showed that the high infiltration group had significantly higher median SUVmax values compared to the low infiltration group (p < 0.001), and a higher incidence of lymph node metastasis (p = 0.039). Sensitivity and specificity of [ 18 F]FDG PET imaging were 0.795 and 0.619 for the high infiltration group, and 0.582 and 0.785 for the low infiltration group, respectively. ROC analysis demonstrated a higher diagnostic accuracy in the high infiltration group (AUC 0.784) compared to the low infiltration group (AUC 0.737). A strong positive correlation was observed between macrophage infiltration levels and PET SUVmax values (p < 0.001), and a significant correlation was also noted between macrophage infiltration and the presence of lymph node metastasis (p = 0.003). In conclusion, increased CD163+M2 macrophage infiltration correlates with higher SUVmax values and more frequent detection of lymph node metastases. These findings suggest that macrophage infiltration may influence [ 18 F]FDG PET imaging performance, potentially contributing to variations in diagnostic accuracy.